LibGeoDecomp: A Grid-enabled Library for Geometric Decomposition Codes - Schäfer, Andreas; Fey, Dietmar (Lecture Notes in Computer Science: Recent Advances in Parallel Virtual Machine and Message Passing Interface, 2008)
In this paper we present first results obtained with LibGeoDecomp, a work in progress library for scientific and engineering simulations on structured grids, geared at multi-cluster and grid systems. Today's parallel computers range from multi-core PCs to highly scaled, heterogeneous grids. With the growing complexity of grid resources on the one hand, and the increasing importance of computer based simulations on the other, the agile development of highly efficient and adaptable parallel applications is imperative. LibGeoDecomp is to our knowledge the first library to support all state of the art features from dynamic load balancing and exchangeable domain decomposition techniques to ghost zones with arbitrary width and parallel IO, along with a hierarchical parallelization whose layers can be adapted to reflect the underlying hierarchy of the grid system. © 2008 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2015-04-16:Pub.2008.tech.IMMD.IMMD3.libgeo_8
Keywords: stencil code; geometric decomposition; hierarchical parallelization